If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(12 + -2e) = 20 (12 * 5 + -2e * 5) = 20 (60 + -10e) = 20 Solving 60 + -10e = 20 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -10e = 20 + -60 Combine like terms: 60 + -60 = 0 0 + -10e = 20 + -60 -10e = 20 + -60 Combine like terms: 20 + -60 = -40 -10e = -40 Divide each side by '-10'. e = 4 Simplifying e = 4
| -10-(-9)-5+(-3)= | | 19x+5y=8 | | 11(2x-2)+8=74 | | 6x-54=-12x+36 | | -(x-75)= | | 3(4x+9)=75 | | 5(n-10)-7n=18 | | 2x+64=180 | | 7w^2-25=62 | | 6(3x+11)=3 | | -3x-10=6-2x | | 10x+4-2-3x=-12 | | 27+4y-9=17y-14-5y | | 7n+4=3n-8 | | 36w^2-25=62 | | 4(y+5)-3y+7=10 | | r^2-12r+35=62 | | 17x-32+24x=12 | | 2(n+1)+3(n+6)=-35 | | x=62square | | 3r^2+16r-35= | | 2(2g-3)=24 | | -5+p=-36 | | x(x-5)+(x-5)=0 | | 4=0.6s | | 11x^2-2x+9=62 | | 4n+5-2n+10=49 | | A(n)=4+(n+1)(6) | | z^5=0 | | 15.35+10.25c=425.35 | | -3(4x+3)+4(6x+1)=43+4x | | (149-3x)=(5x+12) |